Protocol for a multicentre, prospective observational study of elective neck dissection for clinically node-negative oral tongue squamous cell carcinoma (END-TC study). Issue 9 (13th September 2022) - Yanamoto, Souichi; Michi, Yasuyuki; Otsuru, Mitsunobu; Inomata, Toru; Nakayama, Hideki; Nomura, Takeshi; Hasegawa, Takumi; Yamamura, Yoshiko; Yamada, Shin-ichi; Kusukawa, Jingo; Yamakawa, Nobuhiro; Hasegawa, On; et al.
Abstract : Introduction: In early-stage oral tongue squamous cell carcinoma (OTSCC), elective neck dissection (END) is recommended when occult lymph node metastasis is suspected; however, there is no unanimous consensus on the risks and benefits of END in such cases. The management of clinically node-negative (cN0) OTSCC remains controversial. This study, therefore, aimed to evaluate the efficacy of END and its impact on the quality of life (QoL) of patients with cN0 OTSCC. Methods and analysis: This is a prospective, multicentre, nonrandomised observational study. The choice of whether to perform END at the same time as resection of the primary tumour is based on institutional policy and patient preference. The primary endpoint of this study is 3-year overall survival. The secondary endpoints are 3-year disease-specific survival, 3-year relapse-free survival and the impact on patient QoL. Propensity score-matching analysis will be performed to reduce selection bias. Ethics and dissemination: This study was approved by the Clinical Research Review Board of the Nagasaki University. The protocol of this study was registered at the University Hospital Medical Information Network Clinical Trials Registry. The datasets generated during the current study will be available from the corresponding author on reasonable request. The results will be disseminated internationally, through scientific and professional conferences and in peer-reviewed medical journals. Trial registration number: UMIN000027875.